The Relationship Of Islamic Spiritual Mental Development Towards Marriage Age Resistance And The Rate Of Divorce Soldiers - Hasbullah Has Bullah (Program Pascasarjana UMSB, 2022)
The problem in this research are motivated by importance of the Mental Development which is interpreted as an activity to form, maintain, improve and strengthen the mentality of soldiers and civil servants of the Army and their families based on religion, Pancasila, Saptamarga, Soldier Oath, 8 mandatory TNI and Panca Prasetya Korpri and values the nation's struggle through spiritual mental development, mental ideology and mental struggle so as to have a strong mentality in every task implementation. This research is classified as field research, using quantitative methods. The population in this study were Indonesian Army Soldiers in the Infenteri Battalion 131/Brs, Payakumbuh as many as 84 people. Data collection techniques used are questionnaires and documentation. While the data analysis technique used is the Unvariate and Bivariate uni test. The results showed that (1) the results of statistical tests obtained P value (0.023), because P value (0.023) < (0.05), it means that there is a relationship between Islamic Spiritual Mental Development and Marriage Age Resilience in the Infantry Battalion 131/ Brs, Payakumbuh, Result OR = 1.125. Therefore, the implementation of Islamic Spiritual Mental Development in the 131st Infantry Battalion/Brs Payakumbuh is good so that the level of resilience at the age of marriage is also good. (2) The results of statistical tests did not get P value = 0.000, because P value = 0.000 < (0.05), then there is a relationship between Islamic Spiritual Mental Development and the divorce rate in the Infantry Battalion 131/Brs, Payakumbuh and the results OR = 0.800. Therefore, Islamic Spiritual Mental Development in the 131st Infantry Battalion/Brs Payakumbuh is good so that the divorce rate is low. (3) The statistical test results obtained P value (0.018), because P value (0.018) < (0.05), meaning there is The relationship between Islamic Spiritual Mental Development and Concurrent Levels (Marriage Age Resilience and Divorce Rate) in the Infantry Battalion 131/Brs, Payakumbuh and the results of OR = 0.875. Because of that, Islamic Spiritual Mental Development in the Infantry Battalion 131/ Brs, Payakumbuh is good so that the Joint Level (Marriage Age Resilience and Divorce Rate) is also good.